Astrocyte reactivity - Sofroniew, Michael (Henry Stewart Talks, 2023)
Astrocyte reactivity and its effect on different disorders and contexts, Regulating differences of astrocyte reactivity in various disorders, Functions and effects in astrocyte reactivity, Molecularly diversity and context dependency in astrocyte reactivity, Contrasting the long standing dogma of scar tissue formation and axon regeneration prevention by reactive astrocytes, Important functions of reactive astrocytes: regulating CNS inflammation, protecting neural tissue, and facilitating wound repair